Acute Toxicity of Radical Chemoradiation in Patients with Esophageal Carcinoma - Khalid, Esha; Khan, Abdul Wajid; Asar, Muhammad Anas Tahseen; Ilyas, Muhammad Mutayyab; Zahid, Abdul Subhan; Sadaf, Tabinda (Biological and Clinical Sciences Research Journal, 2025)
Currently, management of locally advanced esophageal cancers includes a trimodal approach, which combines radiotherapy, chemotherapy, and surgery. Chemoradiotherapy significantly improved prognosis and survival rates in locally advanced esophageal carcinoma, as demonstrated in several studies, data on its toxicity profile is limited. We assessed the frequency and severity of acute toxicities of Radical Chemo-radiotherapy in patients with esophageal carcinoma. Objective: To evaluate the frequency and severity of acute toxicities associated with radical concurrent chemoradiotherapy in patients with locally advanced esophageal carcinoma and to identify clinical and treatment-related predictors of severe toxicity. Methods: A descriptive prospective study was conducted in the Department of Clinical and Radiation Oncology, Shaukat Khanum Memorial Cancer Hospital & Research Center, Lahore. Pakistan, from 21-June-2024 to 21-April- 2025. A total of 105 patients with esophageal carcinoma undergoing concurrent chemoradiation were analyzed. Clinical, treatment, and dosimetric parameters were recorded. Acute toxicity was graded using CTCAE criteria. The primary endpoint was acute toxicities. Univariate and multivariate logistic regression analyses were performed to identify independent predictors. Results: The mean age was 44.3 ± 10.6 years. Esophagitis (100%) and fatigue ( 92.4%) remain the most common toxicity, with Grade ≥2 esophagitis occurring in 82.9% of patients, and Grade 3 toxicity observed in 38.1%. Hematological toxicities followed this: anemia (69.5%), thrombocytopenia (40%), and low absolute neutrophil count ANC 22.9%. The mean weight loss of approximately 3.4 kg ±3.08 was observed during therapy. Each 1 kg increase in baseline weight reduced the odds of severe esophagitis by 7% (OR 0.93 per kg increase, 95% CI 0.89–0.97, p < 0.001). Only one patient developed esophageal perforation, one patient died with grade 4 dyspnea/pneumonitis, and one died of neutropenic sepsis. Adequate target coverage was achieved across all plans, with a mean PTV V95% of 97.16%, and acceptable organ-at-risk doses were achieved in all plans. 60% of the patients underwent surgery following chemoradiation, and among those, 36.2% patients got a complete response. Only 6.7% patients progressed on the response assessment scan. Conclusion: Toxicity with esophageal chemoradiation is predominantly mucosal and hematological. Acute esophagitis remains the principal toxicity in radical chemoradiation for esophageal carcinoma, with over one-third of patients developing Grade 3 toxicity. Proactive nutritional support, optimization of radiation planning, and close monitoring are essential to improve treatment tolerability along with effective outcomes.